Leicester University - Climb to Success
Promotional video about Leicester University in Leicester, UK. Contains interviews with Prof. Robin White (Law), Prof. Alec Jeffreys (Genetics), Dr. Bob Warwick (Physics and Astronomy), Sir David Attenborough (broadcaster, film-maker and naturalist), Dr. Tony Heagerty (Medicine), Prof. Graeme Barker (Archeologist), Dr. Shearer West (Art History), Dr. Vin Sehmi (Engineering), Prof. Ivan Waddington (Sociology), and Prof. Gerry Bernbaum (Registrar).